(untitled) (KIUT Publication, 2025)
According to the World Health Organization (WHO), every year more than 700,000 people die due to antibiotic-resistant infections. By 2050, this number is projected to reach 10 million. This poses a significant threat not only to healthcare but also to the socio-economic well-being of the global community. Antibiotic resistance negatively affects the reliability of healthcare systems, the duration of disease treatment, and healthcare-related expenses.